RELATIONS BETWEEN THE KOMINTERN AND THE CHILEAN COMMUNIST PARTY (1922-1941) - Grez, Sergio (Revista de Historia Social y de las Mentalidades, 2024)
This article investigates the links between the Communist International (Comintern) and the Communist Party of Chile from 1922 to 1941 based on the hypotheses set forth below. Between 1927 and 1935 the Communist Party of Chile suffered two major ruptures, both in the contents of its national policy and its relationship with the Communist International. The first break, between 1927 and 1933, marked the transition from extraordinary, political autonomy to practically total subjection to the different Comintern bodies which, through gross interference, attempted to convert the Communist Party of Chile into a simple executor of their decisions which were inspired by the politics of “class against class”. The move to popular front policies in 1935 allowed the Chilean party greater margins of autonomy. Although the relationship with the Comintern would remain –essentially– in the terms established at the beginning of the decade, the successes of the Chilean party and the eclipse of the South American Bureau (BSA) of the Communist International, would allow the Communist Party of Chile room for action somewhat less restricted by the Comintern bodies.